Chemical Identification and Antioxidant Screening of Bufei Yishen Formula using an Offline DPPH Ultrahigh-Performance Liquid Chromatography Q-Extractive Orbitrap MS/MS. (15th October 2022) - Wu, Jinyan; Cai, Bangrong; Zhang, Ang; Zhao, Peng; Du, Yan; Liu, Xuefang; Zhao, Di; Yang, Liu; Liu, Xinguang; Li, Jiansheng
Abstract : Chronic obstructive pulmonary disease (COPD) has high morbidity and mortality and presents a threat to human health worldwide. Numerous clinical trials have confirmed that Bufei Yishen formula (BYF), an herbal medicine, can alleviate the symptoms of COPD by reducing oxidative stress-mediated inflammation. However, the active components of BYF remain unclear. We developed an efficient ultrahigh-performance liquid chromatography Q-Extractive Orbitrap mass spectrometry method to identify the composition of BYF and determine its antioxidant profile through an offline screening strategy based on 1, 1-diphenyl-2-trinitrophenylhydrazine (DPPH)-liquid chromatography-mass spectrometry. In total, 189 compounds were identified in BYF extract, including 83 flavonoids, 24 lignans, 20 alkaloids, 15 saponins, 11 terpenoid, 10 saccharides, eight lipids, seven organic acids, two coumarins, two amino acids, and seven other compounds. Among them, 79 compounds were found to have a potential antioxidant activity. In vitro validation indicated that the free radical scavenging activities of rosmarinic acid and calycosin were similar to that of the positive control (DPPH IC50  = 25.72 ± 1.02 and 147.23 ± 25.12  μ g/mL, respectively). Furthermore, calycosin had a high content in serum after the oral administration of BYF, indicating that calycosin might be the major antioxidant compound in BYF.